MODELING OF LEARNING ACTIVITY OF STUDENTS IN PRIMARY CLASS MOTHER LANGUAGE AND READING LITERACY LESSONS (World Bulletin of Social Sciences, 2023)
This article presents ideas about the modeling of students' learning activities in the primary language and reading literacy classes. Also, the content and essence of using innovative technologies in the modeling of students' educational and learning activities in the classes of the mother tongue and reading literacy of the primary grade is highlighted.